Medical relationship with dying patient: specific psychological support - Fassino, Secondo (Medicina e Morale, 1997)
Phisycian-patient interactions, even not verbal, activate emotional and biological transformations acting on body defence systems, peculiarly in terminal phases of disease. Psychological reaction of unhealthy comes from regressive and even progressive defences useful for more advanced adaptative and meaning-giving processes. Psychological reactions of physician are conditioned by defences from anguish and inconscious professional motivations, between impotence and omnipotence feelings. Sentence of defeat induces a constant riformulation of care project: death as care object, not mere end of cares. Accompainment and psychological specific support are required with terminal patient. Adequate strategy implies joining patients trough phases of desease towards death, rather than explorate deep feelings of guilt, undignity and aggressivness. These aspects are proposed only if patient expresses will and skill to copy them; generally it ought to favour an optimal functioning of negation and scission mechanisms and trascendence needs. Accompainment is a "presence" which considers knowledge transferts, no abandonement contract, need of trascendence and meaning, separation dynamics, identity jeopardize etc. This is possibly done not only by psychiatrists and clinical psychologists but even by physicians and infectivologists skilled on "terapeutic relations". Not only cognitive but even emotional and personal aspects must be considered, even in perspective of high burn-out risks. Competences on psychological needs of terminal patients are part of good clinical practice methods: death quality is whithin their goals.